1991
DOI: 10.1620/tjem.164.81
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Duodenal pH and Pancreatic Exocrine Function after Upper G-I Intraluminal Ethanol Administration.

Abstract: of Duodenal pH and Pancreatic Exocrine Function after Upper G-I Intraluminal Ethanol Administration. Tohoku J. Exp. Med., 1991, 164 (1), [81][82][83][84][85][86][87][88][89][90][91] Using 3 outbred dogs with pancreatic, gastric and jejunal fistulas, we examined changes in pancreatic exocrine secretion, duodenal pH and plasma CCK concentration after intragastric or intrajejunal administration of ethanol. Intragastric administration of 20% or 40% ethanol significantly lowered the pH in the duodenal cavity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Reports on the consumption of high-alcohol drinks and the risk for chronic illnesses (17)(18)(19)(20)(21)(22)(23)(24)(25) led us to speculate that (1) in persons who drink high-alcohol beverages, some mechanism other than total grams of ethanol consumed increases the risk for organ injury; (2) low-alcohol beverages (3) something contained in lower-alcohol beverages offers some protection to internal organs. Aside from the direct effects of high or low alcohol content, most recent ecological studies have suggested that wine is effective in reducing the risk of mortality from heart disease because of its antioxidant content (26).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the consumption of high-alcohol drinks and the risk for chronic illnesses (17)(18)(19)(20)(21)(22)(23)(24)(25) led us to speculate that (1) in persons who drink high-alcohol beverages, some mechanism other than total grams of ethanol consumed increases the risk for organ injury; (2) low-alcohol beverages (3) something contained in lower-alcohol beverages offers some protection to internal organs. Aside from the direct effects of high or low alcohol content, most recent ecological studies have suggested that wine is effective in reducing the risk of mortality from heart disease because of its antioxidant content (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments from our laboratory showed that a short duodenal exposure (30 min) of 15% alcohol by volume (ABV) induce low-grade morphological changes in only a small number of duodenal villi tips in rats [5]. Additionally, ethanol induces dysmotility, increases duodenal epithelial paracellular permeability, and stimulates gastric acid secretion as well as pancreatic exocrine secretion [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%